Comparison between 25% dextrose prolotherapy and single dose of platelet rich plasma in the management of pain and improvement of functional outcome in patients suffering from primary knee osteoarthritis: a randomized controlled trial - Deb, Debasish; Singh, Yumnam Nandabir; Singh, Naorem Bimol (International Journal of Advances in Medicine, 2020)
Background: One of the most prevalent and disabling diseases worldwide, which decreases patients' quality of life (QoL) is knee osteoarthritis. However, pharmacological and non-pharmacological treatments, apart from complications, could not desirably control the disease. Limited studies are available in management of primary osteoarthritis of knee with prolotherapy with 25% dextrose and platelet rich plasma (PRP). Objective was to compare between 25% dextrose prolotherapy and single dose of PRP injection in the management of pain and improvement of functional outcome in patients suffering from primary knee osteoarthritis. Methods: A comparative study was conducted to see the effectiveness of 25% dextrose prolotherapy and PRP in primary osteoarthritis (OA) of knee in the management of pain and improvement of functional outcome in sixty-six patients in age group of 50 to 70 years attending PMR department OPD, RIMS, Imphal between october2018 to April 2020. The first group received 6 ml injections of 25% dextrose 3 times at baseline, 1 month and 4th month, whereas the 2nd group received single dose of 5ml PRP at baseline. Results: In both the groups 50 mg of tramadol tablet and isometric strengthening exercise of quadriceps was given. Assessment was done at baseline, at 1, 4 and 8 months by visual analogue scale (VAS) and western Ontario and McMaster university arthritis (WOMAC) index. Statistically significant improvement was noted in VAS (5.91±0.82 to 2.65±0.94) and WOMAC score (45.25±6.68 to 20.25±7.67) at end of 8 month in first group. Conclusion: It was concluded that 25% dextrose was more effective than in management of primary osteoarthritis of knee.